RETRACTED: Radiometeorological research at the Murom Institute - Bulkin Vladislav; Shchukin Georgij; Fedoseeva Elena; Rostokin Il'ya (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001